Avaliação das Habilidades Motoras de Alunos com Paralisia Cerebral: Uso do ASPA-PC - Silva, Michele Oliveira da [UNESP]; Manzini, Eduardo José [UNESP] (My University, 2013)
Due to motor limitations of students with cerebral palsy, in many cases, there is the need to adapt pedagogical resources or indicate among available materials which is more accessible according to their Motor Skills to plan teaching strategies. It is known, however, that for these procedures you must perform an assessment not only able to identify their difficulties in relation to the motor act, but their skills related to resource access and what is expected with the handling. However, it is not so easy to evaluate specific characteristics of each student, since the literature has considered that teachers, even those with training in special education, have had difficulty not only in assessing students with disabilities, but also to consider data assessment to plan an effective intervention in teaching these students. Thus, the aim of this study was to evaluate the motor skills of five students with cerebral palsy using the instrument called ASPA-PC. The results indicated that the use of ASPA-PC enabled the identification of motor skills in relation to access to the materials specifically to each student and therefore was possible : 1) adapting teaching resource; 2) contraindicate the use of a particular feature due to difficulties physical and the energy expenditure of the student performing the movement and 3) indicate more accessible materials to the student, taking into account its design. Furthermore, the evaluation result corroborated to develop teaching strategies for each student according to their characteristics.

Devido às limitações motoras do aluno com paralisia cerebral, em muitos casos, há a necessidade de adaptar os recursos pedagógicos ou indicar dentre os materiais disponíveis, o mais acessível para planejar estratégias de ensino de acordo com suas características motoras. Sabe-se, porém, que para realizar esses procedimentos é preciso realizar uma avaliação capaz de identificar não só suas dificuldades em relação ao ato motor, mas suas habilidades relacionadas ao acesso do recurso e o que se espera com o seu manuseio. No entanto, não é fácil avaliar características tão específicas de cada aluno, já que a literatura tem constado que os professores, mesmo aqueles com formação em Educação Especial têm tido dificuldade não só em avaliar os alunos com deficiência, mas também em considerar os dados da avaliação para planejar uma intervenção efetiva no ensino desses alunos. Dessa maneira, o objetivo desse estudo foi avaliar as habilidades motoras de cinco alunos com paralisia cerebral com o uso do ASPA-PC. Os resultados indicaram que o uso do ASPA-PC possibilitou a identificação das habilidades motoras em relação ao acesso ao material de maneira específica a cada aluno e consequentemente foi possível: 1) adaptar recurso pedagógico; 2) contraindicar o uso de determinado recurso devido às dificuldades físicas e ao gasto energético do aluno em realizar o movimento e 3) indicar materiais mais acessíveis ao aluno, levando em consideração seu design. Além disso, o resultado da avaliação corroborou para elaborar estratégias de ensino para cada aluno de acordo com as suas características.
Assessment of Motor Skills of Students With Cerebral Palsy: Use of ASPA-PC
Keywords: Educacao Especial; Deficiencia Fisica; avaliação escolar